2022
DOI: 10.1177/14749041211062434
|View full text |Cite
|
Sign up to set email alerts
|

A search for the determinants of students’ educational expectations for higher education in four European cities: The role of school SES composition and student engagement

Abstract: Social inequality in students’ educational expectations, a strong predictor of educational attainment, differs substantially between countries. Although education system characteristics are translated into school composition effects, the school level is often forgotten in comparative research. Moreover, to explain school effects, we introduce the concept of student engagement into sociological research on expectations. Results of multilevel analyses (R) on data from 7566 students in 126 high schools in four ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 92 publications
(191 reference statements)
0
1
0
Order By: Relevance
“…Þetta hlutfall hefur verið nokkuð stöðugt undanfarna tvo áratugi (Hagstofa Íslands, e.d.-a, 2018;mennta-og barnamálaráðuneytið, 2016;Menntamálastofnun, 2018). Hvað varðar val nemenda á framhaldsskólum og námsleiðum benda rannsóknir til að meirihluti nemenda líti frekar til bóknáms en starfsnáms (Heiður Hrund Jónsdóttir og Kristjana Stella Blöndal, 2023;Kristjana Stella Blöndal og Bjarney Sif AEgisdóttir, 2013;Kristjana Stella Blöndal o.fl., 2016). Að grunnskóla loknum innritast nánast öll beint í framhaldsskóla (95-97%) en aðeins um 15% nemenda að meðaltali velja starfsnám (Hagstofa Íslands, e.d.-b, 2018;Menntamálastofnun, 2018).…”
Section: Stigveldi Náms Og Skólaunclassified
See 1 more Smart Citation
“…Þetta hlutfall hefur verið nokkuð stöðugt undanfarna tvo áratugi (Hagstofa Íslands, e.d.-a, 2018;mennta-og barnamálaráðuneytið, 2016;Menntamálastofnun, 2018). Hvað varðar val nemenda á framhaldsskólum og námsleiðum benda rannsóknir til að meirihluti nemenda líti frekar til bóknáms en starfsnáms (Heiður Hrund Jónsdóttir og Kristjana Stella Blöndal, 2023;Kristjana Stella Blöndal og Bjarney Sif AEgisdóttir, 2013;Kristjana Stella Blöndal o.fl., 2016). Að grunnskóla loknum innritast nánast öll beint í framhaldsskóla (95-97%) en aðeins um 15% nemenda að meðaltali velja starfsnám (Hagstofa Íslands, e.d.-b, 2018;Menntamálastofnun, 2018).…”
Section: Stigveldi Náms Og Skólaunclassified
“…Spurningakönnun var lögð fyrir á skólatíma í 10. bekk árið 2014 og tóku 1.956 nemendur í 44 grunnskólum þátt, eða um 82% árgangsins. Af þátttakendum voru 52,5% kvenkyns og 47,5% karlkyns og 5% voru með erlendan bakgrunn (báðir foreldrar faeddir utan Íslands) (Heiður Hrund Jónsdóttir og Kristjana Stella Blöndal, 2023). Leyfi fyrir rannsókninni fékkst hjá Persónuvernd (nr.…”
Section: Framkvaemdunclassified
“…Although previous studies have confirmed the positive link between student SES and reading achievement (e.g., Gromada et al, 2021; Li et al, 2020), the relationship between school SES and reading achievement is still controversial, and the cross‐cultural differences in these relationships have not been explored. According to Van den Broeck et al (2022), characteristics of education system are converted into school composition effects, but the school level is often forgotten in comparative research. Moreover, previous studies showed that although family factors play the biggest role in the initial kindergarten reading gap, school conditions contribute more to the differences in reading rates than family (Aikens & Barbarin, 2008).…”
Section: Introductionmentioning
confidence: 99%